已知a是方程x^2+5x-2=0的一个根,(1)则代数式2a^2+10a-7的值为 (2)代数式a^3+6a^2+3a+4的值为

来源:学生作业帮助网 编辑:作业帮 时间:2024/06/14 11:36:28
已知a是方程x^2+5x-2=0的一个根,(1)则代数式2a^2+10a-7的值为 (2)代数式a^3+6a^2+3a+4的值为
x){}KXl++⌴M+tl jyɎUyΧ3^lꆧ{J ú*6ycPP\MbHq \MRX_`g3 V sLA*P'!Mt"00!( u.+ SQ6LDo"8m$&TB $]ck`g_\g%0P`AJ ܃Pa xXJ@Xp2C

已知a是方程x^2+5x-2=0的一个根,(1)则代数式2a^2+10a-7的值为 (2)代数式a^3+6a^2+3a+4的值为
已知a是方程x^2+5x-2=0的一个根,(1)则代数式2a^2+10a-7的值为 (2)代数式a^3+6a^2+3a+4的值为

已知a是方程x^2+5x-2=0的一个根,(1)则代数式2a^2+10a-7的值为 (2)代数式a^3+6a^2+3a+4的值为
已知a是方程x^2+5x-2=0的一个根,
所以a^2+5a-2=0
(1)2a^2+10a-7
=2a^2+10a-4-3
=2(a^2+5a-2)-3
=-3
(2)a^3+6a^2+3a+4
a^3+5a^2-2a+a^2+5a-2+6
=a(a^2+5a-2)+(a^2+5a-2)+6
=6
代数式2a^2+10a-7的值为 -3;代数式a^3+6a^2+3a+4的值为 6.

a是方程x^2+5x-2=0的一个根
a^2+5a-2=0

代数式2a^2+10a-7=2a^2+10a-4-3=2(a^2+5a-2)-3=-3

a^3+6a^2+3a+4
=a(a^2+5a-2)+a^2+5a+4
=a^2+5a-2+6
=6